Mitroflow and Perimount Magna 10 years outcomes a direct propensity match analysis to assess reintervention rates and long follow‐up mortality. Issue 11 (11th September 2019) - Theologou, Thomas; Harky, Amer; Shaw, Matthew; Harrington, Deborah; Kuduvalli, Manoj; Oo, Aung; Field, Mark
Abstract: Objectives: Biological valves are the most commonly used prostheses for aortic valve replacement (AVR) surgery in the UK. The aim of this retrospective observational study was to compare 10‐year outcomes of Perimount Magna and Mitroflow bioprosthesis implanted in a single center. Methods: The medical records of patients undergoing AVR in Liverpool Heart and Chest Hospital between 1999 and 2014 were examined. All data were collected retrospectively, and a propensity match analysis was performed with a ratio 3:1 to analyze 10‐year outcomes. The primary outcomes were all‐cause mortality rates and aortic valve reintervention rates. Results: A total of 2608 patients were included; Mitroflow bioprosthesis was used in 352 patients while Perimount Magna was used in 2256 patients. Median (interquartile range [IQR]) follow‐up for the entire data set was 6.95 (4.99, 9.69) years. After 10 years, the all‐cause mortality rate was higher in Mitroflow cohort 34.8% vs 14.7% ( P < .001). A higher rate of aortic valve reintervention was observed in the Mitroflow cohort (4.7% vs 1%, P < .001). Conclusions: There were significant differences in survival and reintervention‐free survival rate between the two groups considered. The implant of the Perimount Magna valve seems to have a better short‐term and long‐term outcome over Mitroflow valve. Such results require larger studies to be validated.